Evolução temporal da mortalidade materna em adolescentes e adultas jovens no estado da Bahia no período de 2000-2016 - Galvão, Lorena Ramalho (2019)
Introduction: Maternal mortality is a serious public health problem and refers to the death of a woman during or up to 42 days after gestation, due to complications of the pregnancy-puerperal period. Objective: to analyze the temporal evolution of maternal mortality among adolescents and young adults and their correlation with prenatal and childbirth variables, in the state of Bahia, between 2000 and 2016. Methodology: ecological study, in secondary data, with total maternal deaths and total live births, of adolescents and young adults, obtained from the Mortality Information System (SIM) and Live Births (SINASC), from the State of Bahia, during the period from 2000 to 2016. Trend analysis was performed using generalized linear regression, a Prais-Winsten method. The Correlation Coefficient of Spearman was used to analyze the correlation between maternal mortality and prenatal and delivery variables. Results: between 2000 and 2016, maternal mortality among adolescents varied from 28.75 to 104.71 deaths / 100,000 NV and showed a statistically significant decreasing trend, with an annual reduction estimated at -3.53% (95% CI): -6.48% at -0.48%). In young adults, a variation from 43.82 to 87.50 deaths / 100,000 NV and a decline rate of -2.28% (95% CI: -4.62% to + 0.11%) was observed in the same period. From 2004 to 2016, there was a statistically significant decrease in the MMR, with an annual reduction rate of 4.04% and 4.76% among adolescents and young adults, respectively. Maternal death was more frequent among low schooling and due to direct obstetric causes, especially hypertensive disorders and pregnancy ending in abortion. Correlation between prenatal coverage and MMR was identified, that is, the higher the number of visits, the lower the maternal mortality. Conclusions: In the state of Bahia, maternal mortality among adolescents and young adults remains high, but with a significant decrease trend in the period. The results indicate the need for strategies implemented by the Ministry of Health, to improve obstetric care in prenatal, childbirth and puerperium at the national level, and to reduce maternal deaths